Taurine as a possible antiaging therapy: A controlled clinical trial on taurine antioxidant activity in women ages 55 to 70 - Abud, Gabriela Ferreira [UNESP]; De Carvalho, Flavia Giolo; Batitucci, Gabriela [UNESP]; Travieso, Sofia Germano; Bueno Junior, Carlos Roberto; Barbosa Junior, Fernando; Marchini, Julio Sergio; de Freitas, Ellen Cristini [UNESP] (Elsevier, 2022)
Objective: Based on the antioxidant effects of taurine, which are capable of controlling oxidative stress in the aging process, the aim of this study was to investigate the effects of taurine supplementation on biomarkers of oxidative stress in women 55 to 70 y of age. Methods: A double-blind study was conducted with 24 women (61.4 ± 4.2 y, body mass index 31.4 ± 5.1 kg/m²). The participants were randomly assigned to either a control group (GC, n = 11), supplemented with placebo (1.5 g of starch); or a taurine group (GTAU, n = 13), supplemented with taurine (1.5 g), for 16 wk. As primary outcomes, taurine and oxidative stress marker levels were determined in plasma samples. Anthropometry, functional capacity testing, and plasma mineral levels were evaluated as secondary outcomes. The evaluations were performed pre- and postintervention. Food consumption was assessed before, during, and after the intervention. The results were analyzed by two-way repeated analysis of variance measures mixed model, with the Sidak post hoc (P < 0.05). Results: Taurine and superoxide dismutase (SOD, antioxidant enzyme) plasma levels were increased in the GTAU group. SOD levels also were higher than in the GC group after supplementation. Glutathione reductase levels decreased regardless of the intervention. Malondialdehyde levels increased only in the GC participants. Conclusion: Taurine supplementation prevented the decrease in the antioxidant enzyme SOD, suggesting taurine as a strategy to control oxidative stress during the aging process.
Keywords: Aging; Nutritional supplementation; Oxidative stress; Taurine; Therapeutic strategy